PENGAWASAN PELAKSANAAN PROTOKOL KESEHATAN COVID-19 DI OBJEK WISATA ISTANO BASA PAGARUYUNG - M YOGI AZRA; Ernawati Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
Abstract This study aims to describe, analyze and discuss the implementation of monitoring of the Covid-19 health protocol at the Istano Basa Pagaruyung tourist attraction. This type of researchIis aIqualitative descriptiveIstudy. TheItechnique of determining informants is purposive sampling. TheIresults ofItheIstudy found 1) The management of tourist objects at the Pagaruyung Palace made policies according to the Covid-19 health protocol. Such as providing a place to wash hands, wear a mask and keep a distance. 2) Workers direct visitors to the hand washing area, telling each visitor to always keep their distance and check the masks. if visitors are caught not keeping their distance, the officer or worker will directly reprimand or loudspeaker. When visitors in a group of officers or workers give a little leeway by not having to maintain a distance of 1 meter between fellow groups, but the group is prohibited from gathering with other groups of visitors. 3) Before visiting, tourists check their health condition, wear masks, keep their distance and wash their hands.